2019
DOI: 10.1111/medu.13798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deliberate reflection on students’ engagement in learning and learning outcomes

Abstract: Context Reflection in practice is assumed to enhance interest in knowing more about a topic, increasing engagement in learning and learning outcomes. However, this claim lacks empirical evidence, particularly in medical education. The authors investigated the effects of deliberate reflection upon clinical cases on medical students’ engagement in a learning activity and learning outcomes. Methods A three‐task (diagnostic task; learning activity; test) experiment was conducted in August 2017. Seventy‐two fourth‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…The experiment showed deliberate reflection to foster students’ SI relative to giving differential diagnosis, but did not evaluate whether students actually engaged in more learning activities related to the cases. A follow‐up experiment showed that, relative to differential diagnosis, deliberate reflection fostered engagement with a subsequently studied relevant text (as measured by the amount of time spent processing that text) and higher cued recall from this text 5 . These findings suggest that deliberate reflection is an effective learning tool able to foster engagement in learning activities and, ultimately, learning.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The experiment showed deliberate reflection to foster students’ SI relative to giving differential diagnosis, but did not evaluate whether students actually engaged in more learning activities related to the cases. A follow‐up experiment showed that, relative to differential diagnosis, deliberate reflection fostered engagement with a subsequently studied relevant text (as measured by the amount of time spent processing that text) and higher cued recall from this text 5 . These findings suggest that deliberate reflection is an effective learning tool able to foster engagement in learning activities and, ultimately, learning.…”
Section: Introductionmentioning
confidence: 89%
“…Besides being helpful in professional practice, however, reflection is also considered important as a learning tool. It is expected to foster students’ engagement in learning activities, 2,3 and there is some empirical evidence that reflecting upon to‐be‐diagnosed clinical cases can foster medical students’ learning from subsequent study activities relevant to those cases 4,5 . However, this evidence is still preliminary and the mechanisms that underlie such potential positive effects of reflection are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ability to reflect is not only necessary for efficient use of feedback in medical education [ 10 ], it is also essential for clinical practice, and it has been argued that the ability to reflect on one’s own role and performance is a key factor in reliable self-assessment and expertise development [ 11 ]. It therefore seems logical to teach and assess reflection in specialist training [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%